2015
DOI: 10.1111/imm.12376
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and asthma‐associated Proteobacteria, but not commensal Prevotella spp., promote Toll‐like receptor 2‐independent lung inflammation and pathology

Abstract: SummaryRecent studies of healthy human airways have revealed colonization by a distinct commensal bacterial microbiota containing Gram-negative Prevotella spp. However, the immunological properties of these bacteria in the respiratory system remain unknown. Here we compare the innate respiratory immune response to three Gram-negative commensal Prevotella strains (Prevotella melaninogenica, Prevotella nanceiensis and Prevotella salivae) and three Gram-negative pathogenic Proteobacteria known to colonize lungs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 56 publications
8
114
0
3
Order By: Relevance
“…In a birth cohort assessment of the relationship of allergens and bacteria in dust with the development of recurrent wheeze or atopy, Lynch and colleagues found exposure to cockroach, mouse, and, to a lesser extent, cat allergens was protective against recurrent wheeze (30). They further observed that both cockroach and mouse allergens positively correlated with beneficial dust bacterial taxa of Bacteroidetes phylum, such as Prevotellaceae, known to contain a pentaacylated type of LPS (33,34). Brix and colleagues suggested that distinct forms of endotoxin may trigger TLR4 differently, with the result that the pentaacylated endotoxin is protective against asthma and allergic sensitization and the more common hexaacylated variety poses increased risk (35).…”
Section: Discussionmentioning
confidence: 99%
“…In a birth cohort assessment of the relationship of allergens and bacteria in dust with the development of recurrent wheeze or atopy, Lynch and colleagues found exposure to cockroach, mouse, and, to a lesser extent, cat allergens was protective against recurrent wheeze (30). They further observed that both cockroach and mouse allergens positively correlated with beneficial dust bacterial taxa of Bacteroidetes phylum, such as Prevotellaceae, known to contain a pentaacylated type of LPS (33,34). Brix and colleagues suggested that distinct forms of endotoxin may trigger TLR4 differently, with the result that the pentaacylated endotoxin is protective against asthma and allergic sensitization and the more common hexaacylated variety poses increased risk (35).…”
Section: Discussionmentioning
confidence: 99%
“…Microbe-associated molecular patterns (MAMPs) on the surface of bacteria interact with receptors on immune cells to drive inflammation, including lipopolysaccharide (LPS), which interacts with TLR4 on immune cells. 47 LPS that is hexa-acylated is 100-fold more immunostimulatory when bound to TLR4 then LPS that is penta-aceylated.. 48 While penta-aceylated LPS is found in most Gram-negative bacteria, Gammaproteobacteria both penta- and hexa-aceylated LPS. The difference in inflammatory potential between commensal oral Prevotella sp.…”
Section: The Lung Microbiome and Inflammation: A Two-way Streetmentioning
confidence: 99%
“…Данная бак-терия относится к условно-патогенным микроорганиз-мам, способным вызывать инфекции дыхательных путей, мочеполовой системы и бактериемию [13]. Установлено, что легочное воспаление, вызываемое P. nanceiensis, опос-редуется преимущественно активацией Toll-подобного рецептора 2 (TLR2) [14], а чрезмерная активация TLR2 приводит к развитию тахифилаксии к препаратам бета-2 агонистов адреналиновых рецепторов, применяемых для лечения БА [15], и поддержанию нейтрофильной компо-ненты легочного воспаления. Основываясь на этом, можно предположить, что P. nanceiensis может служить фактором риска, обусловливающим рост резистентности к бронхо-литикам у больных БА, приближая фенотип пациентов к таковому при нейтрофильной астме.…”
Section: обсуждение основного результата исследованияunclassified
“…Более выраженное присутствие P. melaninogenica является благоприятным фактором, благодаря способ-ности данной бактерии несколько снижать активность воспаления в дыхательных путях, в частности путем мо-дулирования иммунного ответа, а также препятствовать колонизации патогенных протеобактерий [14].…”
unclassified